In vitro reconstitution of Escherichia coli divisome activation - Radler, Philipp (2022)
Funding Information: We acknowledge members of the Loose laboratory at IST Austria for helpful discussions—in particular L. Lindorfer for his assistance with cloning and purifications. We thank J. Löwe and T. Nierhaus (MRC-LMB Cambridge, UK) for sharing unpublished work and helpful discussions, as well as D. Vavylonis and D. Rutkowski (Lehigh University, Bethlehem, PA, USA) and S. Martin (University of Lausanne, Switzerland) for sharing their code for FRAP analysis. We are also thankful for the support by the Scientific Service Units (SSU) of IST Austria through resources provided by the Imaging and Optics Facility (IOF) and the Lab Support Facility (LSF). This work was supported by the European Research Council through grant ERC 2015-StG-679239 and by the Austrian Science Fund (FWF) StandAlone P34607 to M.L. and HFSP LT 000824/2016-L4 to N.B. For the purpose of open access, we have applied a CC BY public copyright licence to any Author Accepted Manuscript version arising from this submission. Publisher Copyright: © 2022, The Author(s).